Video reportaje sobre el ejercicio de los derechos sexuales y reproductivos de las mujeres en Quito - Medina Mantilla, Andrés Esteban (2016)
This project was realized with the objective of develop new conceptions about the feminist woman thinking, the International Lesbian, Gay, Bisexual, Trans and Intersex Association (ILGA) groups, worker women, single mothers, etc. who are the most affected when it comes to recognizing their rights. The woman is devalued by men since our ancestors time, but the feminists groups came to change this way of thinking that we men have in our minds, assuming as a habit to believe that men are better, smarter, more capable and even the ones who can empower all we have. Other objective of this project is to determine and promote through a video report the rights equality between woman and man. We are people with the same virtues, the same qualities, we have the same brain and therefore we can and we are able to realize any type of activity in our daily lives. This problem also emerges from our mandataries who have despised the ecuadorian woman from many factors; the government has been very critial with them and despite all this situation women are the ones who want to grow the right of gender equality on their rulers. This project is presented as a theoretical reflection about the causes, the background, the consequences of this problem and gives recommendations from the interviewed people who are qualified people in the field and have been recognized for their work in the coun